Precision Compensation Control of a Piezo-Scanning Mechanism - Liu, Shuxin; Jiang, Huhai; Huang, Xiaohong; She, Junchao; Si, Chen; Lv, Shengqiang (Frontiers in Materials, 2022)
In this paper, a controller based on two compensators is developed to support a two-axis piezo-scanning mechanism for tracking control. The hysteresis compensator is designed based on a Prandtl-Ishlinskii hysteresis model in order to reduce the nonlinear hysteresis effect of piezoelectric actuator. Furthermore, to compensate for uncertainties due to parametric variations, hysteresis compensated error and un-modeled dynamics, the uncertainties compensator based on neural network disturbance observer is proposed. The developed controller is verified control performance by experiment. Experimental results show that the proposed hybrid controller can overcome the mentioned nonlinear and uncertainty efficiently and preserve good positioning accuracy.